Stocks prices, macroeconomic variables and market efficiency: 16 years evidence in Malaysia - Arsad, Zainudin; Abd. Wahab, Siti Norhazrina (2007)
Uncovering the dynamic relationship between macroeconomic variables and stock prices is important for policy makers and investors. This paper investigates the interactions between stock market index in Malaysia and five macroeconomic variables for the period from January 1990 to September 2006. The analysis employ co-integration and Granger causality tests to determine long-run equilibrium and short-run lead-lag relationships between the variables. Empirical results show that stock price and macroeconomic variables are co-integrated in the long run before, during and after the Asian Financial Crisis. During the 16-year period stock prices is found to be directly led by money supply and productivity level, and indirectly led by interest rate and price level. In addition, the study found evidence that stock price is a leading indicator for foreign currency exchange rate. Interestingly, the results show that the Malaysian stock market is efficient before and during the crisis period. During the Recovery period, investors can predict the stock prices based on changes in the price level and money supply while policy makers may find it useful to consider movement of stock prices in determining the interest rates.